Time to Serological Cure and Associated Factors Among Syphilis Patients With and Without HIV in a Sexually Transmitted Infections Center, Thailand - Kamolthip Atsawawaranunt (2020)
BACKGROUND: Together with clinical correlation, nontreponemal titers are used to monitor treatment outcomes. Syphilis patients with HIV and without HIV coinfection were found to have different serological responses after treatment. This study aims to determine time to serological cure for treatment of syphilis and factors associated with it in patients with and without HIV. METHOD: A descriptive study of syphilis patients who visited Bangrak STIs Center between January 1, 2007, and December 31, 2016. Univariate analysis was done to determine factors associated with serological outcomes. Survival curve analysis and multivariate Cox regression analysis were applied to compare time to serological cure between patients with various characteristics. RESULTS: Of 497 syphilis patients, 62.1% had serological cure, 2.2% had nonresponse, 4.6% had treatment failure or reinfection, 9.9% had serofast status, and 21.2% were undetermined because of loss to follow-up. The time to serological cure was 110 days (95% confidence interval [CI], 59-163 days) and 102 days (95% CI, 94-110 days) among patients with HIV and without HIV, respectively (P = 0.162). Time to serological cure was significantly faster in early syphilis and baseline titer ≥1:32. After adjustment with the Cox regression model, patients with early syphilis were associated with serological cure with a hazard ratio of 1.75 (95% CI, 1.32-2.32). Time to serological cure among early syphilis patients was significantly longer in HIV-positive than HIV-negative patients (P = 0.002), whereas no difference was observed in late syphilis (P = 0.104). CONCLUSION: Early syphilis was associated with faster time to serological cure. HIV patients with early syphilis took longer time to reach serological cure than did HIV-negative patients, whereas no such a difference was observed in late syphilis.